1996
DOI: 10.1002/(sici)1520-6378(199608)21:4<252::aid-col1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Helmholtz-Kohlrausch effect using the CIELUV formula

Abstract: The Helmholtz‐Kohlrausch effect was predicted by using the CIELUV formula. The predictions were done to the chromatic colors in the whole chromaticity gamut including spectral colors by the Variable Achromatic Color (VAC) and the Variable Chromatic Color (VCC) methods. The effect of adapting‐illuminance change in the perceived lightness of chromatic object colors was also taken into account in the prediction. The prediction equations by the CIELUV formula gave results quite similar to those by the equation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They further concluded that the VCC method is more practical than the VAC, although the previous one is more difficult from experiment point of view. To simplify the process, Nayatani developed equations using the CIELUV formula [10][11][12] instead of the nonlinear color appearance model [13][14]. Nevertheless, the CIELUV formula gave the same effectiveness as those of the nonlinear color appearance model for the various phenomena from the H-K effect.…”
Section: Methodsmentioning
confidence: 99%
“…They further concluded that the VCC method is more practical than the VAC, although the previous one is more difficult from experiment point of view. To simplify the process, Nayatani developed equations using the CIELUV formula [10][11][12] instead of the nonlinear color appearance model [13][14]. Nevertheless, the CIELUV formula gave the same effectiveness as those of the nonlinear color appearance model for the various phenomena from the H-K effect.…”
Section: Methodsmentioning
confidence: 99%
“…That is, for any two color stimuli with the same luminance, the perceived brightness induced by the color stimuli of higher purity will be higher than that of lower purity. Fortunately, Nayatani's has successfully developed the variablechromatic-color (VCC) method in studying the H-K effect [8][9][10][11][12].…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…The author has previously given the following equations on adapting-luminance dependency K(L a ) in the prediction of the Helmholtz-Kohlrasch effect or the brightness-luminance ratio (B/L) effect 8,9 : ) is the same as that of ␤ 1 (L a ) on adapting luminance dependencies in the long-and medium-wavelength responses in the nonlinear color-appearance model. 4,5 Further, K(L a ) is also similar to the physiological response of visual cells to luminous stimuli.…”
Section: Function For Adapting-illuminance Dependenciesmentioning
confidence: 99%